The scientific study of general intelligence : tribute to Arthur R. Jensen - Jensen, Arthur Robert; Nyborg, Helmuth (Pergamon, 2003)
This book celebrates two triumphs in modern psychology: the successful development and application of a solid measure of general intelligence; and the personal courage and skills of the man who made this possible - Arthur R. Jensen from Berkeley University. The volume traces the history of intelligence from the early 19th century approaches, to the most recent analyses of the hierarchical structure of cognitive abilities, and documents the transition from a hopelessly confused concept of intelligence to the development of an objective measure of psychometric g. The contributions illustrate the impressive power g has with respect to predicting educational achievement, getting an attractive job, or social stratification. The book is divided into six parts as follows: Part I presents the most recent higher-stream analysis of cognitive abilities, Part II deals with biological aspects of g, such as research on brain imaging, glucose uptake, working memory, reaction time, inspection time, and other biological correlates, and concludes with the latest findings in g-related molecular genetics. Part III addresses demographic aspects of g, such as geographic-, race-, and sex-differences, and introduces differential psychological aspects as well. Part IV concentrates on the g nexus, and relates such highly diverse topics as sociology, genius, retardation, training, education, jobs, and crime to g. Part V contains chapters critical of research on g and its genetic relationship, and also presents a rejoinder. Part VI looks at one of the greatest contemporary psychologists, Professor Emeritus Arthur R. Jensen as teacher and mentor.